VOCABULARY MASTERY PROBLEMS OF GRADE IX STUDENTS THROUGH KAHOOT - Moh Rafli Rafli; Mawardin M. Said; Moh. Abraham Akbar Eisenring; Mashuri Mashuri (Tadulako University, 2026)
This study aims to identify the problems faced by Grade XI students of MAN Insan Cendekia (IC) Palu in mastering English vocabulary through Kahoot, a game-based digital learning platform. Although Kahoot has been implemented in vocabulary instruction and is recognized for increasing student motivation and engagement, many students still experience difficulties during the learning process. This research employed a qualitative descriptive design. The participants were Grade XI students of MAN IC Palu in the academic year 2025/2026, selected through purposive sampling. Data were collected through observation, questionnaires, and interviews, and analyzed using the Miles and Huberman model, consisting of data reduction, data display, and conclusion drawing. The findings revealed four major categories of problems. First, technical issues, particularly unstable internet connections and slow device performance, frequently interrupted Kahoot sessions. Second, time pressure, as the limited response time caused anxiety and encouraged students to prioritize speed rather than understanding. Third, linguistic challenges, including difficulties in understanding word meanings, spelling, and pronunciation of unfamiliar vocabulary. Fourth, psychological factors, where the competitive features of Kahoot motivated some students but increased anxiety in others. The study concludes that although Kahoot provides an interactive and enjoyable learning environment, its effectiveness in supporting vocabulary mastery depends on several factors, including adequate technological infrastructure, suitable time allocation, clear teacher instructions, and meaningful feedback after quizzes. These findings are expected to help teachers design more effective and supportive vocabulary learning activities using Kahoot in EFL classrooms and improve students’ vocabulary development.